Analysis of a compression refrigeration supplied by photovoltaic power - Ang, Tony Gan; Lasnier, France; Saunier, G.Y.; Reddy, T. A.; Australian Government (Bangkok : Asian Institute of Technology, 1984)
The 'Photovoltaic Refrigeration System Computer Simulation Program' was developed based on theoretical models and experimental observations of an existing system. The system modelled consists of a radiation model, a PV array model, a power regulation model, a battery model and a refrigerator model. The simulation program was developed to study the relationship between the three significant factors that affect the proper operation of a PV refrigeration system. The are, 1. Local weather and ambient conditions. 2. Size of the storage battery and the PV array. 3. User's loading and door-opening behavior. Different scenarios of operating condition were simulated to study its effects on the evolution of the internal refrigerator temperatures and the energy flow of the system. It was observed that high ambient temperature and the presence of a low insolation day decreases the system energetic performance and destabilizes the internal refrigerator temperatures. It was further observed that the choice of a loading profile affects the energy consumption of the compressor. Moreover, it was observed that a proper sizing balance of the battery and the array improves the state of charge of the battery. Experimental observations were also conducted to observe the operation of the regulator and to investigate the temperature stratification inside the refrigerator enclosure. Without door-opening, the internal temperature is uniform throughout. When the time duration of door-opening is equal to 120 sec. and 300 sec., we observed a one-dimensional and a two-dimensional temperature stratification respectively. The experimental results also show that the Ah efficiency of battery charging is 81% and the battery to compressor Ah efficiency is 71%.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources & Development
Thesis (M.Eng.) - Asian Institute of Technology, 1984
Keywords: Refrigeration and refrigerating machinery; Photoelectric cells